JavaServer faces 2.0 [ the complete reference - Burns, Ed; Griffin, Neil; Schalk, Chris (McGraw-Hill, 2010)
"JavaServer Faces 2.0: The Complete Reference features an integrated sample application to use as a model for your own JSF applications, with code available online. The bookexplains all JSF features, including the request processing lifecycle, managed beans, page navigation, component development, Ajax, validation, internationalization, and security. Expert Group Insights throughout the book offer insider information on the design of JSF"--Resource description p